Detection of Fusarium oxysporum f. sp. fragariae from Infected Strawberry Plants - Burkhardt, Alyssa (Plant disease, 2019)
Isolates of the Fusarium oxysporum species complex have been characterized as plant pathogens that commonly cause vascular wilt, stunting, and yellowing of the leaves in a variety of hosts. F. oxysporum species complex isolates have been grouped into formae speciales based on their ability to cause disease on a specific host. F. oxysporum f. sp. fragariae is the causal agent of Fusarium wilt of strawberry and has become a threat to production as fumigation practices have changed in California. F. oxysporum f. sp. fragariae is polyphyletic and limited genetic markers are available for its detection. In this study, next-generation sequencing and comparative genomics were used to identify a unique genetic locus that can detect all of the somatic compatibility groups of F. oxysporum f. sp. fragariae identified in California. This locus was used to develop a TaqMan quantitative polymerase chain reaction assay and an isothermal recombinase polymerase amplification (RPA) assay that have very high sensitivity and specificity for more than 180 different isolates of the pathogen tested. RPA assay results from multiple field samples were validated with pathogenicity tests of recovered isolates